Methotrexate and beta-carotene loaded-lipid polymer hybrid nanoparticles: a preclinical study for breast cancer. (August 2017) - Jain, Ashay; Sharma, Gajanand; Kushwah, Varun; Garg, Neeraj K; Kesharwani, Prashant; Ghoshal, Gargi; Singh, Bhupinder; Shivhare, Uma Shankar; Jain, Sanyog; Katare, Om Prakash
Aim: This work was intended to investigate the targeting potential of fructose-tethered lipid-polymeric hybrid nanoparticles (F-BC-MTX-LPHNPs) co-loaded with beta carotene (BC) and methotrexate (MTX) in breast cancer therapeutics and find out the possible protective role of BC on MTX-induced toxicity.Materials & methods: F-BC-MTX-LPHNPs were fabricated using self-assembled nano-precipitation technique. Fructose was conjugated on the surface of the particles. The in vitro cytotoxicity, sub-cellular localization and apoptotic activity of F-BC-MTX-LPHNPs were evaluated against MCF-7 breast cancer cells. The antitumor potential of F-BC-MTX-LPHNPs was further studied.Results & conclusion: Outcomes suggested that F-BC-MTX-LPHNPs induced the highest apoptosis index (0.89) against MCF-7 cells. Following 30 days of treatment, the residual tumor progression was assessed to be approximately 32%, in animals treated with F-BC-MTX-LPHNPs. F-BC-MTX-LPHNPs are competent to selectively convey the chemotherapeutic agent to the breast cancers. Beta carotene ameliorated MTX-induced hepatic and renal toxicity.